Acerca da utilização do método cientifico nas pesquisas de enfermagem - Isabel Amélia Costa Mendes; Maria Auxiliadora Trevizan (Associação Brasileira de Enfermagem, 1983)
The abstracts of nursing theses and dissertations written in Brazil from 1963 to 1979 and included in "Information on Nursing Research and Researchers" were analyzed and classified. After epistemologic discussion of the subject, the method inductive or deductive used by the author to elaborate his/her thesis was classified on the basis of the summary, and an attempt was made to determine the phase of the method attained in the investigation. It was concluded that the inductive method is the privileged one, even trough it is not used in all its phases, the same occuring with the deductive method, a fact that led the authors to suggest that this factor may be blocking the onset of new problems and the formulation of new theories.